Mediastinal Lymphadenopathy in Visceral Leishmaniasis - Rana, Surinder Singh; Gupta, Nalini; Sharma, Ravi; Kumar, Pankaj (Journal of Digestive Endoscopy, 2021)
Visceral leishmaniasis (VL) usually presents with malaise, fever, weight loss, and hepatosplenomegaly. Lymphadenopathy is rarely reported in patients with VL from India. We report an interesting case of VL, presenting with malaise, fever and weight loss along with isolated mediastinal lymphadenopathy and mimicked tuberculosis. Absence of spleen because of previous splenectomy for symptomatic portal hypertension led to difficulty in establishing the correct diagnosis that was eventually established by endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA).
Keywords: endosonography; tuberculosis; kala-azar; lymph nodes; fine needle aspiration